Kanon literacki: czy to zwierzę metafizyczne czy autentyczny problem? - Lichański, Jakub Z. (Studia Edukacyjne, 2025)
The problem of the “literary canon” should be treated as an element of a lecture on the history of literature, but perceived as a summa of knowledge about works that, in individual eras, played a significant role in determining patterns. A bit like in late antiquity and the Middle Ages, such a role was played by the “Virgilian circle” or later polemics initiated by the famous Querelle des Ancienes et des Modernes. In didactic practice, we should focus on teaching how to read literary texts, and in this respect, the aforementioned rhetoric and rhetorical criticism, as well as traditional descriptive poetics and philology, can be of great help. Currently, with the multitude of achievements, the second determinant is, as Tadeusz Żabski pointed out, “ readers’ tastes”, or more broadly – a literary audience that “wishes” such literature and not another. In this situation, we should rather take care to consciously shape these “reading tastes” in some way, but by defining, in the didactic process, also through literary discussions, the values that cultural texts create and promote.